The THE INFLUENCE OF PRENATAL YOGA TO IMPROVING THE SLEEP QUALITY OF PREGNANT WOMEN IN THIRD TRIMESTER IN THE TAJINAN HEALTH CENTER: PENGARUH PRENATAL YOGA TERHADAP PENINGKATAN KUALITAS TIDUR IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS TAJINAN KABUPATEN MALANG - FAHMI ALFIANI; Rani Safitri; Rifzul Maulina (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Sleep disorder is one of the uncomfortable by third trimester of pregnant women. Sleep disorder include sleeplessness, subjective sleep disorder, poor sleep quality, lack of night's sleep, drowsiness that occurs during the day and awakens at night, the reported prevalence increased to 83.5% after the 8th gestational age month and can increase headaches, dizziness, lack of enthusiasm, activity and emotional disorder. The purpose of this study was to analyze the effect of prenatal yoga on the sleep quality of third trimester pregnant women. The research method used was a pre-experimental one group pre and post test with the Pittsburgh Sleep Quality Index (PSQI). The population of this study were third trimester pregnant women in the working area of Tajinan Health Center with a sample of 32 people using purposive sampling. Data were analyzed using Wilcoxon test with SPSS. The results of the study showed that of the 32 respondents before implementing prenatal yoga, almost all respondents had poor sleep quality, 31 pregnant women (96.9%) and after doing prenatal yoga, almost all respondents had good sleep quality, namely 29 pregnant women (90.6%). Based on the research results, it is hoped that mothers will regularly do prenatal yoga exercises to improve sleep quality until they enter labor.